3-Dimensional Approach on Downtown Area to Improve Urban Space Qualities - Fauzan Permana Noor; Endy Yudho Prasetyo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM), ITS, 2018)
Acting as a Capital of Indonesia, Jakarta has become a core of government, economy, commerce, also cultural hustle of the country. Occupied by 14,464 habitants per km2, its density is twice more than Tokyo, creating a bustling metropolis. The needs of living, commuting and productivity spaces slowly degrading the Green Open Spaces of the city, thus lowering the quality of the city space itself from 32% in 1965 to 9,8% in 2017. Ironically, the active & dense area of downtown Jakarta where the necessity of green spaces are the highest, are the one where such spaces cannot be found. An intervention therefore needed to refine the city spaces. Implementing 3-dimensional approach on one of the core of Jakarta’s downtown area, harmonious with government encouraging a development of walkable city and transit-oriented development, architecture should be able to escalate the quality of space in Jakarta. The design resulted in a simple intervention in the city, that if placed accurately would not only improve the space quality but also integrating areas fractured by other elements of the city.